Editorial of the First Issue - Journal of New Developments in Chemistry - Zhu Qian (Journal of New Developments in Chemistry, 2014)
An inaugural editorial sets scope and standards for the journal, highlighting emerging areas in chemical methods, materials, and interfaces with biology and energy.